ESG disclosure on corporate value in Indonesia: A moderation approach by ownership structure and auditor reputation - Raden Setya Budi Suharto; Marianus Hendrilensio Sanga; Resvina Situmorang; Martina Kaisriani Rupa; Yosef Paseli Dheghu (Trigin Publisher, 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) on company value, with the ownership structure and reputation of auditors as moderation variables in public companies in Indonesia during the 2023–2024 period. This study uses an associative quantitative approach with an ex post facto method, based on secondary data from annual reports, audited financial statements, and ESG ratings from Sustainalytics. The sample was obtained through a purposive sampling technique which included 312 observations of non-financial companies listed on the Indonesia Stock Exchange. Data analysis was carried out using Moderated Regression Analysis (MRA) and tested robustly with the Fixed Effects (FE) and System GMM approach to ensure consistency of results. The results showed that ESG did not have a significant effect on company value, while company size (SIZE) and profitability (ROA) had a significant positive effect. Meanwhile, the auditor's ownership structure and reputation have not been proven to strengthen the ESG relationship with company value. The robustness test confirmed that the results were stable and not affected by endogenicity issues. Theoretically, these findings support the theory of legitimacy and signaling, where ESG practices in Indonesia still function as a means of social legitimacy, rather than economic signals that are clearly appreciated by the market. From a practical perspective, the findings suggest that managers should integrate ESG initiatives with clear financial outcomes and transparent value-creation strategies. Additionally, regulators and policymakers are encouraged to improve ESG reporting standards and market literacy, while investors are advised to interpret ESG information cautiously and in conjunction with conventional financial indicators when evaluating company value.